Socio-cultural determinants of open defecation in rural households of Perambalur district, Tamil Nadu - Kumar, Rakesh; Sinha, Sati P. (International Journal Of Community Medicine And Public Health, 2019)
Background: In many areas of the world, including India, open defecation still remains the predominant norm and poses one of the biggest threats to the health of the people particularly in rural areas. Objectives were to study the prevalence and socio-cultural determinants of open defecation in rural area of Perambalur district. Methods: The present cross-sectional was done in a three randomly selected villages falling under rural field practice area of Department of Community Medicine of Dhanalakshmi Srinivasan Medical College and Hospital in Perambalur district (Tamil Nadu). Data was collected on 330 houses using pre-tested interview schedule developed using SBM-G questionnaire/schedule for ODF verification for household surveys which was modified for present study. Statistical analysis was done using Epi Info version 7 software. Results: Most (89.1%) of the study participants were above 30 years of age. Majority of respondents (39.4%) were illiterate. Prevalence of open defecation was 78.8%. Only 70 (21.2%) houses were using household sanitary latrines. Various reasons reported for open defecation were unawareness about availability of public latrine (41.5%), inadequate water (15.3%), insufficient space for latrine construction (16.9%), inadequate money (10%), considering open defecation better (16.6%) and caste based discrimination (0.4%). The study found sex, education and occupation of head of family to be significantly associated with open defecation. Conclusions: This study highlights the need for implementation well planned behavior change communication strategy to stop the menace of open defecation.